Exploring the efficacy of Benincasa hispida extract on obesity linked inflammatory bowel disease by integrating computational analysis and experimental validations - Santosh B. Patil; Manisha B. Kuvalekar; Deepak A. Yaraguppi; D. S. N. B. K. Prasanth; Sangameshwar G. Halkavatagi; Gururaj B. Tennalli; Mukhatar Ahmed Javali; T. M. Yunus Khan (Scientific Reports)
Abstract The association of obesity with inflammatory bowel disease (IBD) can be understood by the intricate role of pro- and anti-inflammatory cytokines, especially adipokines, which are secreted by adipose tissue and are responsible for IBD because of their structural similarity with tumor necrosis factor-alpha (TNF-α), an important cytokine involved in IBD pathogenesis. The current study was carried out to evaluate the therapeutic potential of Benincasa hispida in obesity-associated IBD. Approximately 18 compounds sourced from Benincasa hispida (Thunb.) were comprehensively analyzed, among which 11 presented favorable drug-likeness scores and adherence to Lipinski’s Rule of Five. Various methodologies, including compound-gene set pathway enrichment analysis, network pharmacology, docking studies, and molecular dynamics simulations, have been employed. Safety assessments via Protox confirmed the nontoxic nature of these compounds, which is crucial for their therapeutic potential. Through Venn diagram analysis of the Gene Card and OMIM databases, proteins associated with obesity and IBD management were pinpointed. Pathway enrichment analysis revealed 810 targets across 192 distinct pathways, with 8 directly related to the pathogenesis of obesity and IBD. Notable therapeutic targets, such as MTOR, were identified through STRING and KEGG pathway database analyses, shedding light on the molecular pathways modulated by these protein targets. Interactions among compounds, proteins, and pathways were visualized via Cytoscape 3.6.1. Furthermore, the compounds were docked with the protein target via AutoDock 4.2, and the compound ajmalin exhibited the highest binding affinity with the MTOR protein, with a binding energy of -7.8 kcal/mol; later, a dynamic study was performed for the ajmaline and protein complex. These findings shed light on the potential efficacy of Benincasa hispida in targeting crucial pathways for managing obesity and IBD. Hence, in vivo studies involving Wistar rats exposed to microplastics and monosodium glutamate (MSG) were carried out to evaluate the potential of Benincasa hispida extracts in mitigating obesity-related IBD. Fecal lipid analysis revealed alterations associated with these conditions, whereas histopathological examinations of the liver and intestine revealed the inflammatory changes induced by MSG and microplastics. The protective effects of this extract on liver and intestinal histology suggest promising avenues for further investigations, emphasizing its potential as a therapeutic intervention for IBD and obesity.